Synthesis, construction, and evaluation of self-assembled nano-bacitracin A as an efficient antibacterial agent in vitro and in vivo - Hong, Wei (Int J Nanomedicine, 2017)
Bacitracin A (BA) is an excellent polypeptide antibiotic that is active against gram-positive bacteria without triggering multidrug resistance. However, BA is inactive against gram-negative bacteria because of its inability to cross the outer membrane of these cells, and it has strong nephrotoxicity, thus limiting its clinical applications. Nanoantibiotics can effectively localize antibiotics to the periplasmic space of bacteria while decreasing the adverse effects of antibiotics. In this study, biodegradable hydrophobic copolymers of poly (d,l-lactide-co-glycolide) (PLGA) were attached to the N-termini of BA to design a novel class of self-assembled nano-bacitracin A (nano-BAs), and their potential as antibacterial agents was evaluated in vitro and in vivo. Nano-BAs had a core-shell structure with a mean diameter <150 nm. Impressively, nano-BAs had strong antibacterial properties against both gram-positive and gram-negative bacteria, and the distribution of antibacterial activity as a function of PLGA block length was skewed toward longer PLGA chains. No cytotoxicity against HK-2 cells or human red blood cells (hRBCs) was observed in vitro, suggesting good biocompatibility. A high local density of BA mass on the surface promoted endocytotic cellular uptake, and hydrophobic interactions between the PLGA block and lipopolysaccharide (LPS) facilitated the uptake of nano-BAs, thereby leading to greater antibacterial activities. In addition, Nano-BA(5K) was found to be effective in vivo, and it served as an anti-infective agent for wound healing. Collectively, this study provides a cost-effective means of developing self-assembling nano-polypeptide antibiotic candidates with a broader antibacterial spectrum and a lower toxicity than commercially available peptide antibiotics, owing to their modification with biodegradable copolymers.